DECISION SUPPORT SYSTEM FOR DETERMINING THE BEST TEACHER USING TOPSIS METHOD (CASE STUDY : SMP NEGERI 1 GALANG) - niar, iinvera; Fahmi, Hasanul (Yayasan Kita Menulis, 2022)
SMP Negeri 1 Galang has activity in determining the best teacher, however, at SMP Negeri 1 Galang the determination of the best teacher still uses the manual method, namely by calculating on paper with a predetermined format. In this case, of course, it takes a long time, considering that there are many junior high school teachers, and also requires many criteria. This is what makes researchers want to conduct research in order to design a decision support system for determining the best teacher using the TOPSIS method at the 1st Galang Junior High School. The Technique for Order Preference by Similarity to Ideal Solution (Topsis) method is one method that is often used in determining a decision, therefore researchers use this method in making a system. With the existence of a decision support system, it can help the school in determining the best teacher, so that the determination of the best teacher can be done accurately and quickly